Libertad de expresión y su impacto en la democracia (2013)
The Political Constitution of the Estados Unidos Mexicanos in its Act 40 states that the Mexican State should be democratic. However, this paper poses as a fundamental problem, how democratic is our country? This is performed according to Dahl’s ideas (1997), taking into account a first requirement, which isequal opportunities for citizens to formulate preferences, and the existence of full freedom of speech, which is expressed in the Act 6 of the Mexican Constitution.